2018
DOI: 10.1093/gbe/evy233
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of polygenic adaptation to high altitude from Tibetan and Sherpa genomes

Abstract: Although Tibetans and Sherpa present several physiological adjustments evolved to cope with selective pressures imposed by the high-altitude environment, especially hypobaric hypoxia, few selective sweeps at a limited number of hypoxia related genes were confirmed by multiple genomic studies. Nevertheless, variants at these loci were found to be associated only with downregulation of the erythropoietic cascade, which represents an indirect aspect of the considered adaptive phenotype. Accordingly, the genetic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 73 publications
(115 reference statements)
4
51
0
Order By: Relevance
“…Appendix A.2. Polygenic adaptation and the benefits of sexual reproduction Several authors have argued that adaptation, especially in humans, may be highly polygenic, resulting from allele frequency shifts across many gene loci (Gnecchi-Ruscone et al 2018;Bergey et al 2018;Boyle et al 2017;Berg and Coop 2014;Hancock et al 2010;Pritchard and Rienzo 2010;. However, there is some debate over the likelihood of such adaptation and proper interpretation of the data (Höllinger et al 2018;Berg et al 2018).…”
mentioning
confidence: 99%
“…Appendix A.2. Polygenic adaptation and the benefits of sexual reproduction Several authors have argued that adaptation, especially in humans, may be highly polygenic, resulting from allele frequency shifts across many gene loci (Gnecchi-Ruscone et al 2018;Bergey et al 2018;Boyle et al 2017;Berg and Coop 2014;Hancock et al 2010;Pritchard and Rienzo 2010;. However, there is some debate over the likelihood of such adaptation and proper interpretation of the data (Höllinger et al 2018;Berg et al 2018).…”
mentioning
confidence: 99%
“…Subsequent studies identified associations between the adaptive PPARA candidate gene and metabolic parameters suggesting reduced fatty acid oxidation (Ge et al, 2012), in addition to greater oxygen utilization and protection from oxidative stress in skeletal muscle (Horscroft et al, 2017;O'Brien et al, 2019). In addition to Tibetan populations, various studies across Sherpa and Central Asian populations provide further support of key adaptive signatures in these populations (Foll et al, 2014;Jeong et al, 2014;Arciero et al, 2018;Gnecchi-Ruscone et al, 2018).…”
Section: Human Genetic Adaptation To High Altitude: Himalayan Highlanmentioning
confidence: 98%
“…Another major selective sweep was detected for the FGF7 gene in a different sheep population adapted to the same region (Gorkhali et al 2016). Despite the identification of several genes showing evidence of strong selective sweeps, highaltitude adaptation is considered to be a complex trait, with underlying polygenic architecture (Yang et al 2017;Gnecchi-Ruscone et al 2018).…”
Section: Genetic Architecturementioning
confidence: 99%
“…There are a number of areas for which further data collection and analysis are warranted. The choice of method applied to identify genes underlying adaptation determines the type of selection signal that can be detected (selective sweep of a single loci vs. allele frequency shifts of many loci), which has led to a focus on selective sweeps, although polygenic adaptation was reported to be a major mechanism underlying the genetic architecture of high‐altitude adaptation (Yang et al ; Gnecchi‐Ruscone et al ). To dissect the polygenic component, data from GWAS, e.g.…”
Section: Genetic Background Of High‐altitude Adaptationmentioning
confidence: 99%